Physical activity and eye diseases. The Beijing Eye Study - Wang, Ya Xing; Jonas, Jost B. (Acta ophthalmologica, 2019)
Purpose To assess associations between the amount of physical activity and the prevalence of ocular diseases. Methods The participants of the population-based Beijing Eye Study underwent a detailed ophthalmological examination and an interview. Physical activity was assessed in a standardized questionnaire. Results Out of 3468 study participants, information on their physical activity was available for 3031 (87.4%) individuals (age: 64.6 ± 9.7 years; range: 50-93 years). In multivariate analysis (regression coefficient r: 0.41), higher physical activity was associated with a lower prevalence of diabetic retinopathy [p = 0.009; standardized regression coefficient beta: −0.05; non-standardized regression coefficient B: −15.7; 95% confidence interval (CI): −27.6, −3.90] after adjusting for younger age, rural region of habitation, lower level of education, lower blood concentrations of triglycerides and low-density lipoproteins and higher blood concentrations of high-density lipoproteins, higher systolic blood pressure, lower body mass index and lower depression score. Other major ocular diseases such as open-angle glaucoma (p = 0.25), angle-closure glaucoma (p = 0.59), nuclear cataract (p = 0.78), cortical cataract (p = 0.54), posterior subcapsular cataract (p = 0.96), retinal vein occlusions (p = 0.93) and central serous choroidopathy (p = 0.39) were not statistically associated with physical activity in that model. The association between higher physical activity and prevalence of age-related macular degeneration (p = 0.04; β: 0.04; B: 4.87; 95% CI: 0.25, 9.50) was marginally significant. Conclusions Higher physical activity and less sedentary lifestyle were associated with a lower prevalence of diabetic retinopathy, while the occurrence of other major ocular diseases such as any type of cataract and of glaucoma, retinal vein occlusions and central serous choroidopathy was statistically independent of physical activity or a more sedentary lifestyle.
Gesehen am 23.05.2019
First published: 18 October 2018